Association of meeting 24-hour movement guidelines with anxiety and depressive symptoms in adults - Tebar, William R. [UNESP]; Aguilar, Beatriz A. S. [UNESP]; Delfino, Leandro D. [UNESP]; Beretta, Victor S. [UNESP]; Brazo-Sayavera, Javier; Silva, Danilo R. P.; Silva, Claudiele C. M. [UNESP]; Ferrari, Gerson; Werneck, André O.; Christofaro, Diego G. D. [UNESP] (Springer Nature, 2024)
There is growing evidence on the association between meeting the recommendations of isolated movement behaviors (physical activity, sedentary time, and sleep) with anxiety and depressive symptoms. However, the joint association of meeting the 24 h movement guidelines with anxiety and depressive symptoms is still unknown. The aim of this study was to analyze the association of meeting 24-hour movement guidelines with symptoms of anxiety and of depression in adults. The sample included 212 participants. Anxiety and depressive symptoms were evaluated using the Hospital Anxiety and Depression Scale (HADS), while physical activity and sedentary time were evaluated by accelerometry, and daily slept hours were self-reported. Age, sex, socioeconomic status, accelerometer wear time, and waist circumference were covariates. Poisson regression models (crude and adjusted by covariates) were used to analyze association between variables. Meeting isolate recommendations of 24-hour movement guidelines were not associated with symptoms of anxiety or depression. However, meeting two or three recommendations was inversely associated with symptoms of anxiety (β= -0.235; 95%CI= -0.447; -0.024); (β= -0.569; 95%CI= -0.853; -0.285) and of depression (β= -0.275; 95%CI= -0.509; -0.040); (β= -0.551; 95%CI= -0.877; -0.224), respectively. Intervention strategies for reducing anxiety and depressive symptoms should target the meeting of more than one movement guidelines, such as increasing physical activity, reducing sedentary time, and promoting adequate sleep time for adults.
Keywords: Epidemiology; Mental health; Physical activity; Sedentary behavior; Sleep